Uji Sensitivitas dan Spesitifitas Immuno Chromatography Test -Tuberculosis (ICT - TB) pada Penderita Tuberkulosis Paru di Kabupaten Bima-NTB - Fitri; Rohmi; Ariami, Pancawati; Kusuma Dewi, Lale Budi (Poltekkes Kemenkes Mataram, 2025)
Background: The problem of Tuberculosis (TB) is a healt problem thathas long been faced by various countries in the world, includingIndonesia. Tuberculosis is an infectious disease caused by infectionwith the germ Mycobacterium tuberculosis. Tuberculosis disease mostlyaffects the lung parenchyma (pulmonary TB). ICT-TB is a serologicaltest that is fast, simple and easy bto operate. The limited of number ofGenexpert MTB in Bima regency is an obstacle in establishing an earlytuberculosis. Objective: To determinan the sensitivity and specificity of the immunochromatography test-tuberculosis (ICT-TB) method in TB patients. Method: This study is an analytical abservational study, with apurposive sampling approach, namely research samples taken fromserum specimens for the ICT-TB method and sputum for GenexpertMTB as standart. The sensitivity and specificity for ICT-TB werecalculated manually using the Mc nemar formula in the 2 x 2 diagnostictest table. Results: The ICT- TB result showed 4 positive IgG respondents and 41negative respondents, while the Genexpert MTB result showed 6 MTBDetected and 39 MTB Not Detected. The ICT-TB sensitivity test resultfor TCM were 50% and specificity 97,44%. Conclusion: ICT-TB method has excellent specificity value. However ,the ICT-TB method examination still has shortcomings that are notfound in the Genexpert MTB method.Recommendation: Further research needs to be carried out usingsamples of tuberculosis positive patients who have not receivedtreatment.